Medication Adherence in a Community Population with Uncontrolled Asthma - Sarah Serhal; Bandana Saini; Sinthia Bosnic-Anticevich; Ines Krass; Frances Wilson; Carol Armour (Pharmacy, 2020)
It is well documented that the use of medications in asthma and allergic rhinitis is often suboptimal, and consequently, patients remain symptomatic. This study aimed to determine the extent and type of medication-related issues contributing to poor asthma control by profiling medication management in those most at risk—a population with clinically uncontrolled asthma. Participants (n = 363) were recruited from Australian community pharmacies, and a dispensed medication history report for the previous 12 months was collected to examine medication adherence and factors affecting adherence. Information was also collected regarding participant asthma control and asthma/allergic rhinitis (if applicable) management. The participants’ mean asthma control score was 2.49 (± 0.89 SD, IQR = 1.20) (score ≥ 1.5 indicative of poorly controlled asthma), and 72% were either non-adherent or yet to initiate preventer therapy. Almost half had been prescribed high doses of inhaled corticosteroid and 24% reported use of oral corticosteroids. Only 22% of participants with concomitant allergic rhinitis were using first line treatment. A logistic regression model highlighted that participant health care concession status and hospital admissions were associated with better adherence. Suboptimal medication management is evident in this at-risk population.